Hybrid Planar 3D Waveguiding Technologies - Fernandez, Marcos D.; Ballesteros, José A.; Esteban, Héctor; Belenguer, Ángel (IntechOpen, 2023)
Traditionally, high-performance communication systems were based on rectangular waveguides (RWGs) to guide high-frequency signals. Newer, efficient RWG-like systems are now available with the added value of low cost, low volume and low weight, together with compactness and ease of manufacture. These systems are based on substrate-integrated waveguides (SIWs), empty SIW (ESIW) and their multiple variations. This book presents successful examples of the use of these systems and the advances in their manufacture, as well as newer techniques that combine 3D metal/plastic printers with the most common planar procedures. The result is a variety of waveguide topologies, applications and manufacturing procedures that may have a strong influence on the design of communication devices and systems.